PARENTING PATTERNS OF CAREER WOMEN IN PROVIDING CHILDREN’S MOTIVATION IN LEARNING - Khotimah, Venna Nurul (International Journal Pedagogy of Social Studies, 2017)
Abstract--Family is the first social group in human life, where he studied and expressed himself as a social human in the interaction with his group. The challenge of the 21st century makes women able to compete with the men in term of occupation. A lot of mothers today choose to play a double role in their life. Ideally, in running her role as a career woman, but also able to perform her duties as a mother. Parental guidance or parenting, especially mothers, plays a role to develop the potential of the child through the patterns of daily habits, both in the school environment, family and community. This is related to the application of parenting in a different family that creates different characters as well. This research used a qualitative approach. The subjects of this research were working mothers who have children who are studying at SMP Laboratorium UPI Bandung with the number of 6 students, 6 working mothers and a teacher. The method used is interview, observation, and documentation. The data about parenting of career women in motivating children learning was taken by using the method of interview and documentation. The results of this study indicated that the implementation of parenting of career women in motivating children’s learning, 2 informants from 6 people majority use the application of authorities parenting pattern, when compared with the application of parenting permissive pattern and parenting indulgent. The four parenting patterns emphasize the motivation of children’s learning both at school and at home. Children’s learning motivation who has career mother in junior Laboratory has a variety depending on the application of mother's parenting pattern in the family.Keywords: Parenting, motivation to learn.